The association between accelerated biological aging and the risk of osteoarthritis: a cross-sectional study - He, Qiang; Luo, Hua; Mei, Jie; Wang, Zhen; Sun, Xin; Wang, Ling; Xie, Chengxin (Frontiers in Public Health, 2024)
Background Biological age (BA) offers an effective assessment of true aging state. The progression of Osteoarthritis (OA) is closely associated with an increase in chronological age, the correlation between BA and OA has not been fully elucidated. Methods This study analyzed data from the National Health and Nutrition Examination Survey (NHANES) 2005–2018. Thirteen commonly used clinical traits were employed to calculate two measures of BA: the Klemera-Doubal method age (KDM-Age) and phenotypic age (Pheno-Age). The residuals of the regression of these ages based on chronological age were calculated as KDM-Age or Pheno-Age acceleration, respectively. OA was determined through self-reported prior diagnoses. The prevalence of OA across different quartiles of BA was compared using weighted chi-square tests and linear trend tests. The association between BA and OA was assessed using weighted multivariate logistic regression models. Results A total of 30,547 participants aged ≥20 years were included in this study, 3,922 (14%) were diagnosed with OA. Participants with OA exhibited higher chronological age, KDM-Age, Pheno-Age, KDM-Age advance, and Pheno-Age advance compared to those without OA (p < 0.001). The prevalence of OA significantly increased with higher quartiles of KDM-Age advance and Pheno-Age advance (P for trend < 0.001). In the fully adjusted model, compared to the lowest quartile (Q1) of KDM-Age advance, the highest quartile (Q4) was associated with a 36.3% increased risk of OA (OR = 1.363; 95% CI = 1.213 to 1.532, p < 0.001). The highest quartile of Pheno-Age advance (Q4) was associated with a 24.3% increased risk of OA compared to Q1 (OR = 1.243; 95% CI = 1.113 to 1.389, p < 0.001). In males and young people, no statistical differences were found in OA risk between the highest and the lowest quartiles of KDM-Age advance (p = 0.151) and Pheno-Age advance (p = 0.057), respectively. Conclusion Adults with accelerated biological aging have an increased risk of OA, particularly among females and older adults.